2020
DOI: 10.1186/s12909-020-1990-3
|View full text |Cite
|
Sign up to set email alerts
|

Implicit expression of uncertainty – suggestion of an empirically derived framework

Abstract: Background: Uncertainty occurs in physicians' daily work in almost every clinical context and is also present in the clinical reasoning process. The way physicians communicate uncertainty in their thinking process during handoffs is crucial for patient safety because uncertainty has diverse effects on individuals involved in patient care. Dealing with uncertainty and expressing uncertainty are important processes in the development of professional identity of undergraduate medical students. Many studies focuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Learners also had opportunities to develop their capacity to manage uncertainty in other, more indirect ways, e.g., through problem-based learning (Maudsley et al 2008 ; Rowan et al 2008 ; Landeen et al 2013 ; Koh et al 2008 ) and simulation (Senette et al 2013 ; Gormley and Fenwick 2016 ; Bintley et al 2019 ; Gärtner et al 2020 ; Groot et al 2020 ; Jowsey et al 2020 ). With regards to the former, researchers recommended that sessions should be actively tutored, and cases not overtly scripted, to support learning around uncertainty (Landeen et al 2013 ; Biley and Smith 1999 ; Maudsley et al 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…Learners also had opportunities to develop their capacity to manage uncertainty in other, more indirect ways, e.g., through problem-based learning (Maudsley et al 2008 ; Rowan et al 2008 ; Landeen et al 2013 ; Koh et al 2008 ) and simulation (Senette et al 2013 ; Gormley and Fenwick 2016 ; Bintley et al 2019 ; Gärtner et al 2020 ; Groot et al 2020 ; Jowsey et al 2020 ). With regards to the former, researchers recommended that sessions should be actively tutored, and cases not overtly scripted, to support learning around uncertainty (Landeen et al 2013 ; Biley and Smith 1999 ; Maudsley et al 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…In case of an inability to detect the implicit uncertainty, it can result in faulty clinical reasoning, thus causing medical errors. 17 There is a lack of a structured format for oral case presentations, where feedback is usually unstructured, depending on the topic, personality of the teacher, time constraints and errors made by students. 18 It is suggested that explicit instructions be given to students for the desired format and expectations, combined with structured feedback; this will help students refine their knowledge and clinical reasoning on a daily basis.…”
Section: Discussionmentioning
confidence: 99%
“…To analyse the students' expression of implicit uncertainty during patient handover, we used our previously developed empirically derived framework 12 based on data from our earlier 360-degree competence-based assessment. 17 The development of this framework was based on qualitative research tools, which enabled the detection of implicit linguistic expressions of uncertainty in the appropriate context for it to be valid.…”
Section: Methodsmentioning
confidence: 99%
“…The complete framework depicting the language of different categories and subcategories of attenuators and strengtheners is described elsewhere. 12 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation